Combined extrusion-printed and laser-induced graphene enabled self-sensing composites with a strategic roadmap toward optimization of piezoresistivity. (October 2021) - Liu, Fu; Li, Liuhe; Wang, Guantao; Wang, Dan; Ding, Xilun; Luo, Sida
Abstract: Laser-induced graphene (LIG) has endowed the assembly and integration of smart devices/structures in next-generation multifunctional composites with unique processing characteristics. Current LIG hybridized composites rely on precedent formation of graphene before integration process, restricting in situ structural design and performance regulation toward multi-scenario sensing applications. Here, an all-computer-aided protocol is creatively proposed with combined extrusion-printing (EP) and LIG for guaranteeing the graphene conversion on filled or pre-patterned polyimide layer, which is effective for balancing manufacturing cost and structural complexity. On the basis of unique dual-modal processing, piezoresistivity of LIG composites is optimized by a roadmap study through sequential and/or combinational control of lasing conditions, levels of pre-deformation treatment, and formats of multi-scaled fractal network. It is discovered that multi-scribing plus pre-bending with specific micro-contact structural design could regularly improve the gauge factor of LIG/composites from 0.67 to 648.8 to assure accurate strain mapping.